PROSEDUR ASAS DALAM PENDAKWAAN KES HUDUD - Ismail, Paizah (Jurnal Syariah, 2008)
Hudud is a capital crime and punishment. For fair justice a straight procedure is crucial so that no one can be made liable to the punishment until everything has been taken into account by the court. This article aims to discuss about the matter and will start by discussing the authority of public prosecution, followed by the principle of reasonable doubt, the assumption of not guilty and the impact of repentance on the procedure.